ANALISIS PENGGUNAAN MEDIA VIDEO DEMONSTRASI UNTUK MENUMBUHKAN MINAT DAN PEMAHAMAN PEMBELAJARAN SKETCHUP SISWA KELAS XI JURUSAN DESAIN PERMODELAN DAN INFORMASI BANGUNAN SMKN 2 BONE - Bahar, Aisyah; Cheriani; Andi Suharman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the use of demonstration video media in fostering students’ interest and understanding of SketchUp learning. This research was descriptive qualitative, with data collected through observation, interviews, and documentation. The subjects were eight 11th grade students from the Building Modeling and Information Design program at SMKN 2 Bone.The results of the study show that the use of demonstration video media was considered effective in fostering students’ interest in learning and improving their understanding of SketchUp. Specifically, participants reported that the demonstration videos made it easier to understand the steps for using tools such as the Line tool and 3D Warehouse; teachers also often re-explained parts of the material that students found difficult to understand; and students frequently rewatched the videos at home for independent practice, reflecting increased motivation and high learning interest. However, there were challenges during the learning process, such as video durations that need adjustment and technical problems like poor audio quality and inadequate speakers. Based on these findings, it can be concluded that demonstration video media play a significant role in fostering interest and improving understanding of SketchUp learning among 11th-grade students in the Building Modeling and Information Design program at SMKN 2 Bone, although improvements in duration and technical presentation quality are needed to maximize effectiveness.